Ad-hoc, mobile, and wireless networks : 18th International Conference on Ad-Hoc Networks and Wireless, ADHOC-NOW 2019, Luxembourg, Luxembourg, October 1-3, 2019, proceedings /: 18th International Conference on Ad-Hoc Networks and Wireless, ADHOC-NOW 2019, Luxembourg, Luxembourg, October 1-3, 2019, proceedings. ([2020]) - Unknown
No abstract available